Q: If 2x - 1 equals 3x plus 4 then x equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x+5=3x+1 -x=-4 x=4

2x = 3x + 1; -x = 1; x = -1.

3x+1+2x-2 = 64 3x+2x = 64-1+2 5x = 65 x = 13

Both equations are equal and so: 3x+1 = 2x+3 3x-2x = 3-1 x = 2 and by substituting y = 7

NM equals 2x + 1, as stated in the question!

Related questions

2x+5=3x+1 -x=-4 x=4

2x = 3x + 1; -x = 1; x = -1.

3x+1+2x-2 = 64 3x+2x = 64-1+2 5x = 65 x = 13

Both equations are equal and so: 3x+1 = 2x+3 3x-2x = 3-1 x = 2 and by substituting y = 7

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

NM equals 2x + 1, as stated in the question!

(1, 1)

3x(2x + 1)

x + 2 = 3x-1 -2x = -3x = 1,5

1

x=1

(5, 1)